Does institutional quality matter for the success of export-led growth? - Sathyamoorthy, Vidhya; Tang, Tuck Cheong (Universiti Putra Malaysia, 2019)
This study aims to examine the influence of institutional quality on Export-led Growth (ELG) strategy with 125 countries' results. Toda and Yamamoto (1995) approach is employed to ascertain their causality between exports and growth, while both contingency table and binary logit models are for determining the influence of institutional quality on ELG from three dimensions, namely political, legal, and economics. This study finds that only 35 countries are supported by ELG hypothesis, while institutional quality does not really matter for the success of ELG, except for economic institutional quality. The results have important implications to policymakers and for further research in this field. © 2019, Universita Putra Malaysia.